2015
DOI: 10.1007/s12053-015-9389-4
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a better energy-efficient automotive air-conditioning system: a review of potential technologies and strategies for vapor compression refrigeration cycle

Abstract: This article presents a review of potential technologies and strategies to develop an energyefficient automotive air-conditioner based on the vapor-compression refrigeration cycle system. This paper is broadly divided into two sections. The first is a review of component optimization (primary and secondary components) that enhances the energy efficiency of the automotive air-conditioning (AAC) system. The second presents a review of operational management and control that efficiently consumes energy in operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…However, even harmful, the energy consumption increases to promote the vehicle thermal comfort is an indispensable condition to meet customer expectations. Therefore, it is important to develop new energy efficient air conditioning systems, which aim to reduce the energy consumption by the vehicle engine, improving its performance as a whole [3].…”
Section: Twbmentioning
confidence: 99%
“…However, even harmful, the energy consumption increases to promote the vehicle thermal comfort is an indispensable condition to meet customer expectations. Therefore, it is important to develop new energy efficient air conditioning systems, which aim to reduce the energy consumption by the vehicle engine, improving its performance as a whole [3].…”
Section: Twbmentioning
confidence: 99%
“…Sukri et al [8] reported that the performance improvement in MAC system with SLHX varied depending upon the refrigerant used and working conditions. A thermodynamic study by Herms [9] on the effects of SLHX in VCR cycle using various refrigerants such as R134a, R22, R290, R410A, R600a and R717 reported that the COP of the system increases if refrigerants R134a, R290 and R600a are used and decreases if refrigerants R22 and R717 are used.…”
Section: Fig 1 Comparison Of Vapour Compression Refrigeration Systemmentioning
confidence: 99%
“…Their result showed that R410A and R407C have thermodynamic performance similar to R‐22. Sukri et al, 5 found the performance of the automotive air conditioning system that can be increased through component optimization and control method. Pottker and Hrnjak 6 found the use of heat exchanger sub‐cooler in VCRS is always increasing cooling capacity, the compressor work and superheating.…”
Section: Introductionmentioning
confidence: 99%